miRNA‐103‐3p‐Hlf regulates apoptosis and autophagy by targeting hepatic leukaemia factor in heart failure - Pengcheng Xue; Yang Liu; Haifeng Wang; Junling Huang; Ming Luo (ESC Heart Failure, 2023)
Abstract Aims Cardiomyocyte apoptosis is an important factor leading to the occurrence and development of heart failure (HF), which is associated with high mortality of patients with cardiovascular diseases. This study aims to investigate the underlying mechanisms of HF in terms of expression and regulation patterns using bioinformatics and experimental validation. Methods and results Two HF datasets were collected: a dataset GSE112056 downloaded from the GEO database (including mRNA and miRNA sequencing data) and another is the laboratory‐owned mRNA dataset. Differential mRNAs and miRNAs in the two datasets were screened using the raw Bayesian approach method. Gene Ontology was used to perform functional enrichment analysis of the differential mRNAs and co‐expression network analysis of the differential mRNAs, combined with nuclear transcription factors in the differential miRNAs and mRNAs for target gene prediction. A HF cell model was constructed using mouse cardiomyocytes (HL‐1), and the role and mechanism of miRNA‐103‐3p‐Hlf (hepatic leukaemia factor) in the process of HF was verified by cell transfection, luciferase reporter gene, WB, and qPCR. We found that Hlf gene expression was decreased in the HF model group and strongly correlated with FYCO1 (FYVE and coiled‐coil domain‐containing protein 1) gene, a phenomenon enriched in apoptotic autophagy‐related pathways. MiR‐103‐3p expression was up‐regulated in the HF model group, and its targeting correlation with Hlf was confirmed by luciferase activity assay. In the HL‐1 cell model, miR‐103‐3p significantly promoted apoptosis and inhibited autophagy in HL‐1 cells (all P < 0.05), and overexpression of the Hlf gene reversed this phenomenon, inhibiting apoptosis and promoting autophagy in HL‐1 cells (all P < 0.05). Conclusions MiR‐103‐3p affects myocardial cells apoptosis and autophagy by targeting Hlf, playing as a potential therapeutic biomarker for HF progression.